The impact of asset purchases in an experimental market with consumption smoothing motives - Jieyi Duan; Nobuyuki Hanaki (Osaka University, Institute of Social and Economic Research (ISER), 2021)
We investigate the effect of preannounced market intervention on an asset price as well as participants' welfare in an experimental frame- work where participants have consumption smoothing motives to trade the asset. The results show that, on one hand, the preannounced inter- vention results in significantly larger overpricing of the asset relative to the rational expectations equilibrium level in periods prior to the intervention compared with the treatment without it. The participants' welfare, measured by the discounted sum of the payoffs at the beginning of the experiment, on the other hand, are not significantly worsened by the intervention.
Keywords: C90; D84; 330; Asset Pricing; Consumption Smoothing; Bounded Rationality; Quantitative Easing